Wishtree - Applegate, Katherine; Santoso, Charles (New York, NY : Feiwel and Friends, an imprint of Macmillan Publishing Group, LLC, 2017)
"A red oak tree and a crow help their human neighbors work out their differences"--
"Red is an oak tree who is many rings old. Red is the neighborhood "wishtree" -- people write their wishes on pieces of cloth and tie them to Red's branches. Along with a crow named Bongo and other animals who seek refuge in Red's hollows, this wishtree watches over the neighborhood. You might say that Red has seen it all. Until a new family moves in. Not everyone is welcoming, and Red's experience as a wishtree is more important than ever"--
A Junior Library Guild selection, November 2017.
Accelerated Reader
Accelerated Reader AR
Keywords: Toleration -- Juvenile fiction; Trees -- Juvenile fiction; Crows -- Juvenile fiction; Wishes -- Juvenile fiction; Friendship -- Juvenile fiction; Toleration -- Fiction; Trees -- Fiction; Crows -- Fiction; Wishes -- Fiction; Friendship -- Fiction; Wishes -- Fiction; Friendship -- Fiction; Trees -- Fiction; Toleration -- Fiction; Crows -- Fiction